A search for the evidence supporting community paediatric practice. Issue 3 (1st March 1999) - Rudolf, M C J; Lyth, N; Bundle, A; Rowland, G; Kelly, A; Bosson, S; Garner, M; Guest, P; Khan, M; Thazin, R; Bennett, T; Damman, D; et al.
Abstract : AIM: Controversy exists regarding the evidence base of medicine. Estimates range from 20% to 80% in various specialties, but there have been no studies in paediatrics. The aim of this study was to ascertain the evidence base for community paediatrics. METHODS: Twelve community paediatricians working in clinics and schools in Yorkshire, Manchester, Teesside, and Cheshire carried out a prospective review of consecutive clinical contacts. Evidence for diagnostic processes, prescribing, referrals, counselling/advice, and child health promotion was found by searching electronic databases. This information was critically appraised and a consensus was obtained regarding quality and whether it supported actions taken. RESULTS: Two hundred and forty seven consultations and 1149 clinical actions were performed. Good evidence was found from a randomised controlled trial or other appropriate study for 39.9% of the 629 actions studied; convincing non-experimental evidence for 7%; inconclusive evidence for 25.4%; evidence of ineffectiveness for 0.2%; and no evidence for 27.5%. Prescribing and child health promotion activities had the highest levels of quality evidence, and counselling/advice had the lowest. CONCLUSIONS: An encouraging amount of evidence was found to support much of community paediatric practice. This study improved on previous research in other specialties because actions other than medications and surgery were included.